Mastering the infinite game : - Hampden-Turner, Charles (Capstone publishing limited, 1997)
This book is a unique exploration of the social, cultural and economic differences between East and West. It goes beyond the usual studies of Eastern management to look at the underpinning philosophies and argues that western corporations play to win (a finite game) while the Tiger economies play to learn (an infinite game)